Removal of 2,4-dichlorophenoxyacetic acid using tio2-sugarcane bagasse biochar photocatalyst (TIO2-SBBC) in aqueous solution. - Clarito, Jovelyn Antona
2,4-Dichlorophenoxyacetic acid is considered a persistent emerging pesticide which contaminates soil, sediments, surface water and even underground water. Thus, degradation of this pollutant is a must to avoid further accumulation and exposure in the environment, endangering the health of the organisms. In this study, TiO2-sugarcane bagasse biochar (SBBC) photocatalyst which were synthesized via the solvothermal synthesis method and was used in the removal of the organic pollutant. The adsorption and the photocatalytic activity of the TiO2-SBBC were assessed against the herbicide in a closed system under different light sources. Higher 2,4-D removal was attained at decreasing pH and pollutant concentration and increasing photocatalyst dosage. Photocatalytic degradation was performed at varying operational parameters under visible light 99.95% removal, dark conditions 91.43% removal, and UV light source, 87.65% removal. The reaction kinetics were determined according to the Langmuir-Hinshelwood (L-H) pseudo-first order kinetic model. The TiO2-SBBC photocatalyst showed enhanced adsorption and photodegradation processes under visible light source (94.35%), UV light (41.25%), and dark condition (54.34%) in 60 minutes of irradiation time. Higher pollutant removal was achieved at lower solution pH, which can be attributed to the transformation of the carboxylic groups to negatively-charged carboxylate groups (-COO-). The Fourier transform infrared results confirm this transformation and the major involvement of carboxyl groups in the adsorption process. The results of the study revealed that the adsorption and photocatalytic mechanism successfully removed the 2,4-Dichlorophenoxyacetic acid pollutant. The prepared TiO2-SBBC photocatalyst can be used as an excellent catalyst in the removal of aqueous pollutants under any light source.